Membrane processes : a technology guide - Cardew, P. T. (Royal Society of Chemistry, 1998)
Discussing the technology and its applications, Membrane Processes: A Technology Guide investigates the differing requirements of industry today. Driven by increasing water quality demands, the technological spotlight is now on the application of membranes to potable water, and several significant examples of filtration processes are given. Encompassing the fundamentals of design and operation of membranes, feasibility of use and economics as well as applications in water, paint and other industries, this coverage of the key aspects of membrane technology will be welcomed by technologists, engi.